Total Glycosides of Cistanche deserticola Promote Neurological Function Recovery by Inducing Neurovascular Regeneration via Nrf-2/Keap-1 Pathway in MCAO/R Rats - Wang, Fujiang; Li, Ruiyan; Tu, Pengfei; Chen, Jianping; Zeng, Kewu; Jiang, Yong (Frontiers in Pharmacology, 2020)
Background: The traditional Chinese medicine Cistanche deserticola has been reported to be valid for cardiovascular and cerebrovascular diseases. However, its active components for the protection of ischemic stroke are not clear. We aimed to explore the active components of C. deserticola against ischemic stroke as well as its potential mechanisms. Methods: we investigated the brain protective effects of extracts from C. deserticola, total glycosides (TGs), polysaccharides (PSs) and oligosaccharides (OSs) in a rat model of middle cerebral artery occlusion-reperfusion (MCAO/R). 2, 3, 5-Triphenyltetrazolium chloride (TTC) staining was used to assess the cerebral infarction volume, and Evans blue assay was adopted to assess the blood-brain barrier (BBB) permeability. Then, the expressions CD31, α-SMA, PDGFRβ, SYN, PSD95, MAP-2, ZO-1, claudin-5, occludin, Keap-1 and Nrf-2 were analyzed by western blotting or immunofluorescence, and the activities MDA, SOD, CAT and GSH-Px were analyzed by kits. Results: TGs treatment remarkably decreased neurological deficit scores and infarction volumes, promoted angiogenesis and neural remodeling, and effectively maintained blood-brain-barrier integrity compared with the model group. Furthermore, TGs significantly decreased MDA levels and increased antioxidant activities (SOD, CAT and GSH-Px) in brains. Meanwhile, TGs remarkably downregulated Keap-1 expression and facilitated Nrf-2 nuclear translocation. On the contrary, no protective effects were observed for PSs and OSs groups. Conclusion: TGs are the main active components of C. deserticola against MCAO/R-induced cerebral injury, and the protection is mainly via Nrf-2/Keap-1 pathway.